Internalisasi Nilai-Nilai Karakter Keislaman Dari Qs Al Hujurat Ayat 11-12 Dalam Menghadapi Fenomena Hate speech Di Lingkungan Pergaulan Peserta Didik - Wathroh Mursyidi; Nur Laily Fauziah; Faznah Faznah (Departement of Mathematics Education, 2024)
The verses of Qur’an, which are the way of life for a Muslim, teach the rules for communicating in relationships. In the midst of the flow of digital communication and the shift in Islamic and national character values that we are currently facing, language styles and ways of communicating between individuals have deviated from what they should be. The aim of this research is to conduct a literature review related to instilling character values based on QS. Al Hujurat verses 11-12 in dealing with the phenomenon of hate speech in students' social environment. The research method used is a literature review. Data was obtained by collecting various research articles that have similar research interests. The results of this research show that the phenomenon of hate speech or hate speech in simple form among students can be prevented by instilling character values based on QS. Al Hujurat verses 11-12 so as to minimize disputes between students.